7 Risk factors for the development of left ventricular systolic dysfunction in patients receiving trastuzumab therapy – a single centre retrospective review. (5th October 2017) - McInerney, A; Hughes, D; Morris, P; McAdam, BF
Abstract : Introduction: Trastuzumab, a humanised monoclonal antibody against HER 2 has revolutionised the management of HER 2 positive breast cancer. Left ventricular systolic dysfunction (LVSD), however, remains one of its use limiting complications. We attempted to identify risk factors for LVSD in our cohort of patients who have received trastuzumab for the treatment of breast cancer in anticipation of starting a cardio-oncology service in our institution. Methods: A retrospective study of patients who received trastuzumab between 2010 and 2015. Baseline characteristics, CV risk factors, pre-chemotherapy CV medications, chemotherapy regimes, and ECHO data were analysed to identify risk factors for the development of LVSD. Continuous variables were compared using a t-test with categorical variables compared using a Fisher test. Results: Between 2010 and 2015, 134 patients completed trastuzumab treatment for breast cancer. Data were available for 109. All were female. The average age at first dose was 52 years (SD 12.8). Ninety nine (91%) were invasive ductal carcinoma with 6 (5.5%) being lobular. Eleven (10%) had metastatic disease, 51 (46.8%) had node positive disease and 47 (43.1%) were node negative. LVSD, defined as LVEF decrease >10%, occurred in twelve patients (11%). Differences between the two groups are outlined in table 1 . Patients who received both an anthracycline and trastuzumab had a statistically significant increased risk of LVSD (58.34% versus 25.7% p=0.038). No other statistically significant risk factors were identified. The use of beta blockers, ACE inhibitors/ARB's and other cardiovascular drugs did not appear to confer any protective effect in the development of LVSD in our cohort. Numbers receiving these drugs were however small. Two patients had their trastuzumab discontinued and one had a dose reduction due to LVSD. Seven (59%) patients did not have full recovery of their LVEF at last ECHO. None of these patients received disease modifying therapies. Conclusion: LVSD was seen in 11% of our cohort, in keeping with expected rates of trastuzumab related cardiotoxicity. As expected, anthracyclines use identifies a cohort at higher risk of LVSD and interestingly, none of the traditional CV risk factors identified patients who went on to develop LVSD. Additionally, no drugs could be identified as offering any protective effect from LVSD in our single centre cohort. Further work is required to aid identification of patients at increased risk of LVSD.